Perkembangan Bank Syariah PAsca UU 21 Tahun 2008 - Prasetiyo, Luhur (IAIN Ponorogo, 2012)
Islamic banking system still grows continuously over time in various countries, including Indonesia. Although it was a bit late, if it was compared to another, Islamic banking system began to develop in Indonesia in the early 1990’s. At that time, Islamic banking, however, was still running with its all characteristics based on the rule without adequate law. Islamic banking began to be recognized legally as the legalization of UU Perbankan 1992, and it was followed by its deregulation in 1998, and Islamic banking in Indonesia finally got its full legality after legalization of UU Perbankan Syariah in 2008. UU Perbankan Syariah as a new law certainly has significance for the development of Islamic banking in Indonesia. Based on the BI statistics, Islamic banks, especially Bank Umum Syariah after legalization of UU Perbankan Syariah, has been growing significantly, among in the number of banks, total assets, and total financing. Unfortunately, the growth of PLS (profit and loss sharing) doesn’t occupy a significant position in total financing of Islamic banks, whereas PLS is core system in Islamic banking.